Processability of 4D printable modified polycaprolactone with self-healing abilities. (2019) - Invernizzi, Marta; Turri, Stefano; Levi, Marinella; Suriano, Raffaella
Abstract: Shape memory polymers (SMPs) with their responsive nature are good candidates for the field of sensors and actuators, in particular for soft robotics. To enhance their durability and mimic natural tissues, self-repairing properties are required. The 4D printing of shape memory polymers has already been demonstrated but the coupling with the self-healing behavior was recently presented. The aim of this work was to study the processability of a SMP with thermally induced healing abilities by digital light projection (DLP) technology to obtain 4D printed smart objects. Polycaprolactone (PCL) was co-crosslinked with 2-ureido-4[1H]-pyrimidinone (UPy) units in this newly prepared material showing shape memory and self-healing functionalities, both thermally triggered. To verify the possibility to 4D print the reactive mixture, a rheological characterization was carried out. Printed PCL/UPy-based objects showed a stiffness similar to pure PCL-based ones, and healing properties comparable to cast specimens. Tensile characterization was performed to confirm the suitability of this material for the soft robotic field. This potential application was also supported by the printing and damaging of an opposing thumb: shape memory functionalities were still preserved after healing, making these printed actuators suitable for the production of components for human-machine interactions